Integrated modeling of solutions in the system of distributing logistics of a fruit and vegetable cooperative - Dubinin, Ylia Yrievna (Business: Theory and Practice, 2014)
A mechanism of preparing rationalistic solutions in the system of distributing logistics of a fruit and vegetable cooperative has been studied considering possible alternatives and existing limitations. Belonging of separate operations of the fruit and vegetable cooperative to technological, logistical or marketing business processes has been identified. Expediency of the integrated use of logistical concept DRP, decision tree method and linear programming in management of the cooperative has been grounded. The model for preparing decisions on organizing sales of vegetables and fruit which is focused on minimization of costs of cooperative services and maximization of profits for members of the cooperation has been developed. The necessity to consider integrated model of differentiation on levels of post gathering processing and logistical service has been revealed. Methodology of representation in the economical-mathematical model of probabilities in the tree of decisions concerning the expected amount of sales and margin for members of the cooperative using different channels has been processed. A formula which enables scientists to describe limitations in linear programming concerning critical duration of providing harvest of vegetables and fruit after gathering towards a customer has been suggested.